2011
DOI: 10.1111/j.1740-0929.2011.00875.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplementation of soy sauce oil and Ca salts of fatty acids on rumen fermentation, milk production and conjugated linoleic acid in milk of dairy cows

Abstract: Eight cows were used to evaluate the effects of supplementation of soy sauce oil (SO) or Ca salts of fatty acids (FA) on rumen fermentation and milk production. The control diet (CO) consisted mainly of hay, corn silage and a concentrate. In the experimental diets, 400 g/day per cow of SO or FA (soybean oil and rapeseed oil) was supplemented to the CO diet. Experimental period for the three treatments was 14 days, and milk samples were taken during the last 2 days and rumen sample was taken on the last day. Dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 18 publications
3
6
1
Order By: Relevance
“…Approximately 100 mL of the fluid sample was stored at −30°C until subsequent analysis. For the analysis of volatile fatty acids (VFA), the rumen fluid samples were acidified with 1.5 mol/L sulfuric acid containing 12% metaphosphoric acid, and measured by gas chromatography as previously described (Shibata et al . 2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 100 mL of the fluid sample was stored at −30°C until subsequent analysis. For the analysis of volatile fatty acids (VFA), the rumen fluid samples were acidified with 1.5 mol/L sulfuric acid containing 12% metaphosphoric acid, and measured by gas chromatography as previously described (Shibata et al . 2011).…”
Section: Methodsmentioning
confidence: 99%
“…1999; Belury 2002; Pariza 2004). There have been many attempts to increase milk CLA levels through increasing the fat content of the diet, and we previously reported that supplementation with soy sauce oil and Ca salts of fatty acids increased the CLA concentration in milk fatty acids (Shibata et al . 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Cenkvári et al (2005) reported that when sheep were fed a diet composed of alfalfa hay and concentrate and supplemented with 75 g.day -1 of calcium salts of linseed oil (5.4% of dry matter), the total VFA concentration in the rumen fluid measured 3 h after feeding did not change, the acetate:propionate ratio decreased and the butyrate and valerate levels increased. Shibata et al (2011) reported that fed cows with 400 g.day -1 of CSFA had decreased total VFA 2 h after feeding with CSFA. Table 6.…”
Section: Level Of Calcium Salts Of Fatty Acidsmentioning
confidence: 99%
“…Ruminal pH in the present study was within the optimal range (6.1-6.7) to ensure normal A c c e p t e d A r t i c l e growth of major rumen microbes [21], and other ruminal parameters including ammonia and VFA were not greatly affected by the administration of kg of soy sauce oil (Table 4). However, Shibata et al [14] reported that rumen fermentation was slightly inhibited by soy sauce oil at a lower level of administration (0.4 kg/d), as was observed for decreased VFA concentration. The reason for the different responses between the two studies is not clear, although the response in feed intake should be examined not by direct ruminal administration, but by a feeing study, and allowable supplementation levels should be proposed for the application of soy sauce oil.…”
Section: Discussionmentioning
confidence: 90%
“…Preliminary evaluation of soy sauce oil as a dietary lipid for ruminants was carried out by Shibata et al [14]. They indicated that soy sauce oil has no negative effect on dry matter (DM) intake, milk yield and composition, while the proportion of CLA in milk fat increased with ruminal administration of soy sauce oil at 0.4 kg/d.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%